Evaluation of osteogenic potential of demineralized dentin matrix hydrogel for bone formation - Nessma Sultan; Soher Nagi Jayash (BMC, 2023)
Abstract Objectives Dentin, the bulk material of the tooth, resemble the bone's chemical composition and is considered a valuable bone substitute. In the current study, we assessed the cytotoxicity and osteogenic potential of demineralized dentin matrix (DDM) in comparison to HA nanoparticles (n-HA) on bone marrow mesenchymal stem cells (BMMSCs) using a hydrogel formulation. Materials and methods Human extracted teeth were minced into particles and treated via chemical demineralization using ethylene diamine tetra-acetic acid solution (EDTA) to produce DDM particles. DDM and n-HA particles were added to the sodium alginate then, the combination was dripped into a 5% (w/v) calcium chloride solution to obtain DDM hydrogel (DDMH) or nano-hydroxyapatite hydrogel (NHH). The particles were evaluated by dynamic light scattering (DLS) and the hydrogels were evaluated via scanning electron microscope (SEM). BMMSCs were treated with different hydrogel concentrations (25%, 50%, 75% and neat/100%) and cell viability was evaluated using MTT assay after 72 h of culture. Collagen-I (COL-I) gene expression was studied with real-time quantitative polymerase chain reaction (RT-qPCR) after 3 weeks of culture and alkaline phosphatase (ALP) activity was assessed using enzyme-linked immune sorbent assay (ELISA) over 7th, 10th, 14th and 21st days of culture. BMMSCs seeded in a complete culture medium were used as controls. One-way ANOVA was utilized to measure the significant differences in the tested groups. Results DLS measurements revealed that DDM and n-HA particles had negative values of zeta potential. SEM micrographs showed a porous microstructure of the tested hydrogels. The viability results revealed that 100% concentrations of either DDMH or NHH were cytotoxic to BMMSCs after 72 h of culture. However, the cytotoxicity of 25% and 50% concentrations of DDMH were not statistically significant compared to the control group. RT-qPCR showed that COL-I gene expression was significantly upregulated in BMMSCs cultured with 50% DDMH compared to all other treated or control groups (P < 0.01). ELISA analysis revealed that ALP level was significantly increased in the groups treated with 50% DDMH compared to 50% NHH after 21 days in culture (P < 0.001). Conclusion The injectable hydrogel containing demineralized dentin matrix was successfully formulated. DDMH has a porous structure and has been shown to provide a supporting matrix for the viability and differentiation of BMMSCs. A 50% concentration of DDMH was revealed to be not cytotoxic to BMMSCs and may have a great potential to promote bone formation ability.